Internal Control Opinion Shopping and Audit Market Competition - Newton, Nathan J.; Persellin, Julie S.; Wang, Dechun; Wilkins, Michael S. (The Accounting Review, 2016)
ABSTRACT This study examines the extent to which audit clients successfully engage in internal control opinion shopping activities and whether audit market competition appears to facilitate those activities. Regulators have long been concerned about the impact of both audit market competition and opinion shopping on audit quality. We adopt the framework developed in Lennox (2000) to construct a proxy to measure the tendency that clients engage in internal control opinion shopping activities. Our empirical results suggest that clients are successful in shopping for clean internal control opinions. In addition, we find evidence that internal control opinion shopping occurs primarily in competitive audit markets. Finally, our results indicate that among auditor dismissal clients, opinion shopping is more likely to occur when dismissals are made relatively late during a reporting period and when audit market competition is high. Our findings have implications for the current policy debate regarding audit quality and audit market competition.